Effect of side branch on gas separation performance of triptycene based PIM membrane: A molecular simulation study. (March 2020) - Ghasemnejad-Afshar, Ehsan; Amjad-Iranagh, Sepideh; Zarif, Mahdi; Modarress, Hamid
Abstract: In this study ab initio calculations, molecular dynamics (MD) and Monte Carlo (MC) simulation techniques are used to investigate the structural properties of triptycene based polymers of intrinsic microporosity (PIMs), consisting of polyimide branched with the side groups: C4 H9, C3 H7, CH3 and CF3, to evaluate their performance as polymeric membrane for separation of gases, O2, N2, CO2, CH4 and H2 S, which are the constituents of natural gas and their separation is of high industrial interest. In the course of MD simulation, initially, the branched polyimide membranes are built to obtain the PIMs' model. Then the low-density membrane models undergo a consecutive simulation procedure of compression and relaxation to achieve the experimental density of equilibrated membrane. The structure of the constructed membranes is analyzed by calculating: dihedral angles, radius of gyration, fractional free volume, accessible free volume, cavity size distribution, and surface area. The behavior of the membranes against penetration and permeation of the studied gases is determined by evaluating the diffusion and solubility coefficients of the gases and by employing MD and MC simulation techniques, respectively. Comparison of the structural properties of the membranes shows that the PIM membranes with larger side branch groups in their polymeric chain structure are more rigid and therefore, due to restriction in chain packing and cavity formation between polymer chains, the free volume in the membrane's structure increases which as a result would promote the diffusion and permeation of gases into the membrane, where, the obtained results indicate that the membrane with C4 H9, as the largest side branch in its polymer chain, has the greatest diffusivity and permeation. Also, the highest selectivity for all studied binary gas mixtures is manifested by the PIM membrane with C4 H9 at its side branch, however, for (CO2 /CH4 ) and (H2 S/CH4 ) binary mixtures CF3 as the side branch of PIM membrane represents an acceptable selectivity. The obtained results illustrate that in addition to the membrane free volume, other parameters are influential in gas separation by these polymeric membranes which require further consideration. These parameters include gas adsorption, specific surface area of the membrane for adsorption, the size of gas molecules and their interaction with the PIM membranes which need to be investigated and discussed in the light of the obtained results. To the best of knowledge, based on a thorough investigation of the literature, no similar work can be cited which includes detailed properties of PIM membranes at the atomic scale by using quantum mechanical and simulation techniques in order to elucidate the behavior of PIMs for gas separation. Highlights: Comparison of the obtained results for the studied gases through PIM membranes indicated consistency with the experimental.. Increasing the size of the side branch in the PIMs caused narrower distribution in dihedral angle profile.. The diffusion coefficient is affected by the effective diameter of gas molecule and their interaction with the polymer matrix. The membrane with C4 H9 as the side branch indicated the best selectivity in separation of (O2 /N2 ). The membrane with CF3 as the side branch showed an acceptable performance in separation of (H2 S/CH4 ) and (CO2 /CH4 ).